Ionic conductivity study on carboxymethylcellulose blended with polyvinyl alcohol incorporated with ammonium bromide based solid biopolymer electrolytes as application in electrochemical device - Norfatihah, Mazuki (2020)
In the present work, a polymer blend carboxymethyl cellulose (CMC)-polyvinyl alcohol (PVA) based solid biopolymer electrolytes (SBEs) incorporated with various amount of ammonium bromide (NH4Br) is reported. The electrolyte films comprised of CMC-PVA which act as host polymer and NH4Br as the proton provider were successfully prepared via the casting technique. The interactions between host polymer and ionic dopant were tested and confirmed via Fourier Transform Infrared Spectroscopy (FTIR) analysis where shifting and changes in intensity of the peaks were observed. The X-ray Diffraction analysis proved that the sample became amorphous when up to 20 wt. % NH4Br was introduced into the system. The thermal properties of the SBEs were studied using Differential Scanning Calorimetry (DSC) and Thermo Gravimetric Analysis (TGA). It was observed in the TGA that the decomposition temperature (Td) increased with the addition of NH4Br which indicates the improvement in thermal stability of biopolymer electrolytes. Meanwhile, the DCS analysis revealed that the glass transition temperature (Tg) also decreased as the NH4Br content increased and this suggests that the present sample has good thermal stability. Based on impedance analysis, the SBEs of the present work showed an improvement in ionic conductivity when 20 wt. % of NH4Br was introduced into the system where the optimum room temperature ionic conductivity of 3.21 ± 0.005 x 10-4S cm-1was achieved. The temperature dependence for all of the SBEs were discovered to obey the Arrhenius behavior with the value of the regression approaching unity (R2~ 1). The increment of NH4Br caused the activation energy of the CMC-PVA-NH4Br system to decrease in an inversely proportional way to the ionic conductivity trend. The dielectric behavior of the SBEs were determined using electrical modulus spectra and dielectric permittivity which revealed a non-Debye behavior. The transport properties of the present SBEs were investigated via Impedance fitting analysis approach. These methods revealed that the ionic conductivity of the CMC-PVA-NH4Br based biopolymer electrolyte is primarily influenced by the ions diffusion coefficient and ionic mobility. The cationic transference number for the sample with the highest ionic conductivity was determined using the dc polarization method. Non-blocking reversible electrodes were used to identify the proton (H+) transference number (tH+) which was observed to be 0.31. This indicates that cationic conduction was the predominant source of the conducting species. Consequently, the sample with highest conductivity (20 wt. % NH4Br) was used to fabricate an electrical double layer capacitor (EDLC) device. Based on the Linear Sweep Voltammetry (LSV) technique, the electrochemical potential window of the most conducting biopolymer electrolyte showed an operating voltage up to 1.55 V. The specific capacitance (Csp) of the CMC-PVA-20 wt. % NH4Br biopolymer electrolyte was calculated from Cyclic Voltammetry (CV) curve and the results showed good agreement with the Csp obtained from Galvanostatic Charge-Discharge (GCD). The average value of power density and energy density was observed to be at ~31.36 W kg -1and ~1.19 Wh kg-1, respectively. Thus, these findings suggest that the biopolymer electrolyte-based CMC-PVA-NH4Br system has a good potential for applications in energy storage devices.